2021
DOI: 10.1038/s41467-020-20452-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabatic heating governs the seasonality of the Atlantic Niño

Abstract: The Atlantic Niño is the leading mode of interannual sea-surface temperature (SST) variability in the equatorial Atlantic and assumed to be largely governed by coupled ocean-atmosphere dynamics described by the Bjerknes-feedback loop. However, the role of the atmospheric diabatic heating, which can be either an indicator of the atmosphere’s response to, or its influence on the SST, is poorly understood. Here, using satellite-era observations from 1982–2015, we show that diabatic heating variability associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
4
19
0
Order By: Relevance
“…This indicates that SST anomalies in this region could also respond to cloud cover (e.g., Xie and Carton, 2004). Our result agrees with the recent results from Nnamchi et al (2021) which showed that the precipitation which is a good proxy for the diabatic heating, leads SST variability in the equatorial Atlantic. This means that the atmosphere forces the ocean, even though the region north of 10 • S is dominated by ocean dynamics.…”
Section: Discussion and Summarysupporting
confidence: 92%
“…This indicates that SST anomalies in this region could also respond to cloud cover (e.g., Xie and Carton, 2004). Our result agrees with the recent results from Nnamchi et al (2021) which showed that the precipitation which is a good proxy for the diabatic heating, leads SST variability in the equatorial Atlantic. This means that the atmosphere forces the ocean, even though the region north of 10 • S is dominated by ocean dynamics.…”
Section: Discussion and Summarysupporting
confidence: 92%
“…In conclusion, the combination of a large moisture flux from the equatorial Atlantic toward the Guinea Coast and a more destabilized atmosphere over the Guinea Coast leads to an enhanced rainfall response to AEM in the GC+ models compared to GC− models. Moreover, according to Nnamchi et al (2021b), the rainfall response to the AEM is maximum at the location of the mean intertropical convergence zone (ITCZ). The CMIP6 models present a spurious southward position of the mean ITCZ position relative to the observations during the boreal summer.…”
Section: Evaluation Of the Performance Of The Gcms In Simulating The Jas Rainfall Pattern Related To The Atlantic Niñomentioning
confidence: 99%
“…The similarities include SST anomalies that are most pronounced in the eastern half of the basin, and the role of the Bjerknes feedback (Bjerknes, 1969), in which equatorial SST anomalies induce changes in equatorial surface winds that further amplify the pattern. Subsequent research, however, identified several differences with ENSO, including the relatively weak role of the Bjerknes feedback (Nnamchi et al., 2021; Richter et al., 2017) and a strong influence from off‐equatorial processes in some events (Foltz & McPhaden, 2010; Lübbecke & McPhaden, 2012; Richter et al., 2013). Partly motivated by these differences, the term “Atlantic Zonal Mode” (AZM) has gained traction in recent years and will be used in the present study.…”
Section: Introductionmentioning
confidence: 99%